Analysis Of The Role Of Burnout In The Relationship Between Workload And Work-Family Conflict (Wfc) On The Performance Of Healthcare Workers At Air Saga Community Health Center - Siswani, Siswani; Sinta, Sinta; Purwadhi, Purwadhi; Restiani Widjaja , Yani (Jurnal Indonesia Sosial Sains, 2025)
Puskesmas as a first-level health facility has the main responsibility in providing promotive, preventive, curative, and rehabilitative services to the community. Air Saga Health Center is one of 9 health centers under the Belitung Regency Health Office. This health center serves a working area consisting of 6 villages/sub-districts with a population of 5,304 people and the outpatient service load reaches more than 15,000 visits a year. To carry out its duties, the Air Saga Health Center is supported by 57 health workers and non-medical employees, including 18 nurses, 2 dental nurses, 13 midwives, as well as 2 dentists and 2 general practitioners. The organizational structure and role of human resources in the health service system greatly affect the effectiveness of the organization as a whole. When workload increases without adequate human resource management, the risk of burnout becomes high. is a condition of emotional, physical, and mental fatigue that occurs due to prolonged work pressure, and has been proven to reduce the quality of health workers' services. Some studies show that burnout does not stand alone, but is often mediated by other factors, such as high workload and Work-Family Conflict (WFC). International research shows that Work-Family Conflict and workload simultaneously affect and degrade the performance of nurses and other medical personnel, both in developing countries such as Iran and developed countries such as South Korea and China. Studies in Indonesia also show that work-family conflicts, burnout, and work stress contribute significantly to the decline in nurse performance in various hospital and health center contexts